Penyuluhan dan Pelayanan Kesehatan Sebagai Upaya Memperbaiki Manajemen Hipertensi Pada Lansia Di Kelurahan Jembatan Lima Kecamatan Tambora Jakarta - Sisca, Sisca; Hartanti, Monica Dwi; Setyaningrum, Dyah Ayu Woro; Lestari, Indah Widya; Ilona, Florinda; Chendrasari, Julian; Parwanto, ML Edy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The incidence of hypertension increases with age. Alterations in function and structure in peripheral vascular system are thought to be the cause of high prevalence of hypertension in the elderly. Holistic, patient-centered management of hypertension is needed to prevent deaths from heart failure. This community service aimed to find out the level of knowledge about hypertension in residents of Jembatan Lima Sub-district, Tambora District, West Jakarta. Using a questionnaire, the level of knowledge was studied in 48 participants cross-sectionally. Blood pressure measurements were also carried out to describe the incidence of hypertension in that area. There was a low level of knowledge about hypertension among participants and this had an impact on increasing the risk of hypertension. Fifty-two percent of participants had normal blood pressure, whereas 48% participants were diagnosed as hypertension. Based on demographic data of participants obtained during the event, age, sex, education level and type of work were significantly increasing the risk of hypertension. Results from this community service conclude that the lack of knowledge of hypertension especially in the elderly can increase the risk of hypertension. In order to improve the quality of managing hypertension in the elderly in Jembatan Lima Village, Tambora District, West Jakarta, it is recommended that counseling and discussion groups to be held annually, especially among the elderly.